Effect of Cross Nanowall Surface on the Onset Time of Explosive Boiling: A Molecular Dynamics Study - Rasoul Fallahzadeh; Fabio Bozzoli; Luca Cattani; Muhammad Waheed Azam (Energies, 2024)
Explosive boiling is a fast-phase transition from an ultra-thin liquid film to vapor under an extremely high heat flux, which typically has been studied using the molecular dynamics simulation (MDS) method. The present MDS study investigated the explosive boiling of a liquid argon nanofilm over different solid copper surfaces with different nanowall patterns, including parallel and cross nanowalls. For each surface, atomic motion trajectories, the number of liquid and vapor argon atoms, heat flux, and, mainly, the onset time of explosive boiling were investigated. The simulation results indicated that explosive boiling occurs earlier on parallel and cross nanowall surfaces than on an ideally smooth surface, regardless of the topology and configuration of the nanowalls. Moreover, the results revealed that by using the cross nanowall surfaces, the onset time of explosive boiling decreased by 0.7–4% compared to the parallel nanowall surfaces. In addition, it was found that the onset time of explosive boiling strongly depends on the potential energy barrier and the movement space between nanowalls for both parallel and cross nanowall surfaces. Furthermore, the simulation findings showed that even though increasing the height of cross nanowalls increases the heat flux and temperature of the fluid argon domain, it does not necessarily result in a shorter onset time for explosive boiling. These findings demonstrate the capability of cross nanowall surfaces for explosive boiling, thereby being utilized in future surface design for thermal management applications.